Role of intestinal Angptl4 on liver health - Lim, Shan Chun (Nanyang Technological University, 2023)
In recent years, nonalcoholic fatty liver disease (NAFLD) has been the main cause of liver transplantation, and it affects a quarter of the world’s population. A new concept, “leaky gut” syndrome, is seen as an important factor for NAFLD progression since it causes gut-liver axis dysfunction. A recent study on a peanut allergy model demonstrated that intestinal Angptl4 is responsible for the increase in intestinal epithelial permeability. Due to this and Angptl4’s association with lipid metabolism and liver steatosis, this study aims to investigate the effect of intestinal Angptl4 knockout on high-fat diet (HFD)-induced leaky gut-associated NAFLD. We utilized a novel Angptl4vil-/- mouse genotype to characterize the changes in intestinal permeability and liver oxidative stress via 4-HNE IHC staining, RT‒qPCR for the expression of tight junctions, and eWAT, liver and intestine histology. The results have been promising in reversing the impacts of the LIDPAD diet, namely: 1) a decrease in adipocyte count; 2) an increase in adipocyte cell size; 3) an increase in lipid peroxidation in hepatocytes and; 4) an decrease in tight junction expression under LIDPAD diet. However, further investigation is required to increase the reliability of findings via an increase in sample size and further confirmation experiments.